Pengaruh Penerapan Model Problem Based Learning dalam Pembelajaran Matematika terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar Negeri 11 Pontianak Timur - Elsa Susandi Putri; Siti Halidjah; Rio Pranata (Journal on Education, 2024)
This research aimed to analyze the influence of implementing the problem-based learning model in mathematics learning on the learning outcomes of IV-grade students in SD Negeri 11 Pontianak Timur. The research method used experimentation in the form of quasiexperimental design. The population of this research was all fourth-grade students which consisted of 2 classes. The sample was IV A class, which consisted of 23 students, and the IV B class consisted of 23 students. The technique of data collection applied in this research was the measurement technique, and the tool of data collection is a multiplechoice test with 30 questions. Based on data analysis, the average final test for the experimental class = 58.326 and the average for the final test for the control class = 57.065. The results of hypothesis testing using the t-test obtained t_count= 10.0791, while dk (23+23-2=44) with a level of α = 5% obtained t_table= 2.07387 which means t_count>t_table, then Ha is accepted. Based on the results of the effect size (ES) calculation, the ES value = 0.77. Thus, it can be concluded that the application of the problem-based learning model in mathematics learning has an influence on the learning outcomes of IV-grade students in SD Negeri 11 Pontianak Timur with the percentage of 76.